Karakterisasi santan instan bubuk yang dibuat menggunakan filler Na-CMC dari bacterial cellulose: Characterization of instant coconut milk powder made using Na-CMC fillers from bacterial cellulose - Santosa, Budi; Sriwaningsih, Endang Rusdiana; Wulang, Domu (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2023)
The development of the times demands the problem of food being available in a fast and ready-to-eat time, one of which is the problem of providing coconut milk. Making coconut milk during this time requires a long process and takes a long time. To answer this problem, instant coconut milk powder is the solution. This product has the advantages of long shelf life, easy packaging, easy storage and easy to transport due to reduced volume and weight. This study aims to determine the role of Sodium - Carboxymethyl Cellulose (Na-CMC) from bacterial cellulose as a filler in the manufacture of instant coconut milk powder combined with maltodextrin. The experimental design used in the study was a Single Factor Completely Randomized Design, the factor was the proportion between Na-CMC and Maltodextrin consisting of 4 levels of C1 (Na-CMC 0% : Maltodextrin 20%), C2 (Na-CMC 5% : Maltodextrin 15%), C3 (Na-CMC 10% : Maltodextrin 10%), C4 (Na-CMC 15% : Maltodextrin 5%), C5 (Na-CMC 20% : Maltodextrin 0%). Observed parameters of moisture content, fiber content and solubility. The results showed the highest water content of instant coconut milk powder in the C5 treatment (Na-CMC 20% : Maltodextrin 0%) of 11.51%, the highest fiber content of 0.34% in the C5 treatment (Na-CMC 20% : Maltodextrin 0%), while the solubility was highest in the C1 treatment (Na-CMC 0% : Maltodextrin 20%) of 40.50%.